Nghiên cứu biến tính đá ong bằng lantan làm vật liệu hấp phụ xử lý ion florua và photphat trong nước thải - Thảo, Phương; Trung, Đỗ Quang; Thu Hương, Đặng Thị; Dũng, Công Tiến (Vietnam Journal of Chemistry, 2016)
Removal of fluoride and phosphate from water has been studied and conducted, but high fluoride or phosphate content from wastewater has not well controlled. In order to increase adsorption capacity for fluoride and phosphate, natural laterite ore was studied to activate by impregnating with lanthanum nitrate. Activation condition and characterization of the adsorbent was investigated. Maximum fluoride and phosphate adsorption capacity of the activated laterite was found to be 3.00 mg/g and 5.30 mg/g, respectively. Both of fluoride and phosphate adsorption process are good at acid and neutral medium and reduce at alkaline medium. Effect of co-ions including bicarbonate, sulphate, fluoride and phosphate onto the adsorption was also studied. Keywords. Fluoride removal, phosphate removal, laterite, activated, adsorption, wastewater treatment.